Youth resilience and modern neurotechnologies: new horizons of psychological support - Sodolevska, Valeriia (Psychosomatic Medicine and General Practice, 2025)
The full-scale war in Ukraine has had profound socio-psychological consequences for a generation of young Ukrainians. Loss of security, experience of losses, constant feeling of threat and uncertainty form a high level of stress and emotional exhaustion among young people [1]. In these conditions, the concept of resilience – the ability of a person to adapt to difficult circumstances while maintaining psychological functioning and development potential – is gaining special attention [2]. Research shows that resilience is not an innate trait, but is formed due to a combination of cognitive, emotional and social factors [3]. Young people who have self-regulation skills, maintain social connections and have a conscious life goal demonstrate higher resistance to stress [4]. At the same time, modern science offers new technological tools for developing resilience – in particular, VR therapy, bio- and neurofeedback. These methods activate physiological mechanisms of self-regulation, reduce hyperactivation of the sympathetic nervous system and improve emotional stability [5, 6]. In working with young people, such technologies have proven effective in reducing anxiety levels, improving sleep quality, and concentration [7, 8]. Thus, the combination of psychological and neurophysiological approaches creates new horizons in the field of psychological support for young people. Developing resilience through neurotechnology can become not only a tool for preventing mental disorders, but also an important factor in the restoration of society after war. Keywords: resilience; youth; mental health; war; neurotechnology; VR therapy; biofeedback; neurofeedback; heart rate variability (HRV); self-regulation; psychological support; emotional stability; rehabilitation; psychophysiological adaptation.